Preliminary design and development of grain dryer grain fired by microwave - Norasyikin Binti Ali (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project aimed is to determine the potential of obtainning dryer grin in a microwave energy. Grain drying is one of the most energy consuming processes on farms. It has also a lot of potential for energy savings. Grain drying can be divided into different processes that is heat generation, which are casued by the hot dryer surfaces.